Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2190/de.43.2.d
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Study on Factors That Influence Parents' Knowledge about Their Children's Alcohol Use

Abstract: Previous research has shown that parents underestimate their children's substance use. The aim of the present work was to analyze parental estimation of their children's use of alcohol in five countries from northern, central, and southern Europe, and to explore the variables that influenced this perceptual bias. The sample comprised 1181 parent-children dyads living in Sweden, Slovenia, the Czech Republic, Spain, and Portugal. In accordance with the findings of previous studies, we found high parental underes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The study, which focused on 3,587 parents and 7,065 children between 11 and 19 years in five European countries (Sweden, Slovenia, Czechia, Spain, and Portugal), helped Fernandez-Hermida et al (2013) show that parents’ underestimation (79.1%) of their children’s access to and consumption of substances, is a risk factor associated with consumption.…”
Section: Resultsmentioning
confidence: 99%
“…The study, which focused on 3,587 parents and 7,065 children between 11 and 19 years in five European countries (Sweden, Slovenia, Czechia, Spain, and Portugal), helped Fernandez-Hermida et al (2013) show that parents’ underestimation (79.1%) of their children’s access to and consumption of substances, is a risk factor associated with consumption.…”
Section: Resultsmentioning
confidence: 99%
“…(1) Biological and physiological factors, (nicotine has been noted as more addictive than alcohol, marijuana and cocaine [5]); (2) Socio-demographic factors (relapse is more likely in e.g. smokers with an earlier initiation age [6], smokers with a lower socio-economical status [7], or smokers who live with other smokers [8]); and (3) Psychiatric factors (especially the presence of comorbidities such as depression [9] or another drug abuse problem [6]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has evidently shown that parents across countries are often unaware of their adolescents' involvement in substances ( Ahern, Kemppainen, & Thacker, 2016 ; Bogenschneider, Wu, Raffaelli, & Tsay, 1998 ; Bylund, Imes, & Baxter, 2005 ; a Taiwanese study, see Chang, Lee, Miao, et al, 2013 ; a cross-national study, see Fernandez-Hermida, Becoña, Secades-Villa, Juan, & Sumnall, 2013 ; Fisher, Bucholz, Reich, et al, 2006 ; Green et al, 2011 ; Jones et al, 2017 ; Langhinrichsen, Lichtenstein, Seeley, et al, 1990 ; McGillicuddy, Rychtarik, Morsheimer, & Burke-Storer, 2007 ; a Canadian study, see Williams, McDermitt, Bertrand, & Davis, 2003 ; Yang, Stanton, Cottrel, et al, 2006 ). One may assume that parents who are aware of their deviant behaviors may take appropriate and preventive actions to avoid further misbehaving ( Beck & Lockhart, 1992 ; Kerr, Stattin, & Burk, 2010 ).…”
Section: Introductionmentioning
confidence: 99%